Dear Reviewer 2: Go F' Yourself. (25th June 2020) - Peterson, David A. M.
Abstract : Objectives: The objective of this study was to empirically test the wide belief that Reviewer #2 is a uniquely poor reviewer. Methods: The test involved analyzing the reviewer database from Political Behavior . There are two main tests. First, the reviewer's categorical evaluation of the manuscript was compared by reviewer number. Second, the data were analyzed to test if Reviewer #2 was disproportionately likely to be more than one category below the mean of the other reviewers of the manuscript. Results: There is no evidence that Reviewer #2 is either more negative about the manuscript or out of line with the other reviewers. There is, however, evidence that Reviewer #3 is more likely to be more than one category below the other reviewers. Conclusions: Reviewer #2 is not the problem. Reviewer #3 is. In fact, he is such a bad actor that he even gets the unwitting Reviewer #2 blamed for his bad behavior.